Hubungan Tingkat Pengetahuan Kesehatan Reproduksi terhadap Kesiapan Menarche pada Remaja Putri Awal - Era Fazira; Rize Budi Amalia; Reny I’tishom (EMBRIO: Jurnal Kebidanan, 2022)
Menarche is the first monthly cycle in early adolescence. To face menarche, young women need mental and physical preparation. There are several factors that influence the preparation for menarche, one of which is information on reproductive health. The level of reproductive health information will affect the preparation and behavior of young women in facing their first monthly cycle. This research was conducted so as not to cause adverse effects on young women who are facing menarche. This review aims to show the relationship between the level of information about reproductive health with menarche readiness in adolescent girls aged 10-14 years. This study is an in-depth observational study with a cross-sectional examination plan. The number of research subjects was 104 young women aged 10-14 years who had experienced menarche at SDN Mandesan 02 and SMPN 1 Selopuro. The information collected has been tested with the factual Fisher Exact Test. The results showed that almost all respondents (97.1%) had good information. most respondents (96.9%) who are ready to face menarche have good information and all respondents (100%) who are not ready to face menarche have good information and all respondents (100%) who are not ready to face menarche have good information about reproduction health. Conclusion: there is no relationship between the level of knowledge about the welfare of conception with menarche preparation in early adolescence.